The estimation of emission from the gateways to Surakarta City, Indonesia using the software of Mobilev 3.0 as the basis for an action plan of emission control - SUNARTO SUNARTO; WIRYANTO WIRYANTO; WIDHI HIMAWAN (Nusantara Bioscience, 2016)
Abstract. Sunarto, Wiryanto, Himawan W. 2016. The estimation of emission from the gateways to Surakarta City, Indonesia using the software of Mobilev 3.0 as the basis for an action plan of emission control. Nusantara Bioscience 8: 288-296. Surakarta is the center for activities of a pseudo area unit called Greater Solo, which includes several regencies nearby, bordering on Surakarta City. As a result, many commuters enter Surakarta daily, most of whom using personal vehicles, causing high emission from mobile sources, especially during working days. Heavy traffic can be seen in several main gateways to the city, namely two-way traffic section of Slamet Riyadi Street, Adi Sucipto Street, Ir Sutami Street, Yos Sudarso Street and Mangunsarkoro Street. Emission from transportation on those streets is higher than that of Central Business District (CBD). The objective of this study was to estimate the emission from mobile sources on the gateways to Surakarta City as an input for an action plan to reduce urban emission. The number of vehicles on the five gateways was counted by direct observation using CCTV belonging to the Office of Transportation, Communication and Information of Surakarta City in 2012. The estimation of emission from transportation was done using software of Mobilev 3.0. Data conversion was done using Microsoft Excel. The results showed that in 2012, the total Average Daily Traffic (ADT) on the five gateways was 442,959 units of vehicles. The highest ADT was found on Ir Sutami Street, which was 110,537 units/day. Most of the vehicles were motorcycles (75%) and personal passenger cars (17%). Other gateways had similar composition, but their exact numbers varied. This composition was an obvious indicator of community preference for personal vehicles over public transportation. The estimate of emission on the five gateways was 84.87 ton/yr of CH4, 1,829.56 ton/yr of CO, 46,212.03 ton/yr of CO2, 946.29 ton/yr of HC/NMVOC, 190.13 of NOx ton/yr, 14.75 ton/yr of PM10 and 2.52 ton/yr of NH3. The amount of emission was influenced by the number and composition of vehicles on each street. The total consumption of fuel on the five gateways was 14,884.35 ton/yr, mostly by motorcycles (34%) and personal passenger cars (29%). The composition of fuel was 61% of gasoline and 39% of diesel. Most of the time, the traffic scenario was heavy except for Ir Sutami Street and Mangunsarkoro Street in which the traffic was stopped and go.